1998
DOI: 10.1002/(sici)1098-2396(199812)30:4<409::aid-syn8>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Localization of pontine PGO wave generation sites and their anatomical projections in the rat

Abstract: A number of experimental and theoretical reports have suggested that the ponto-geniculo-occipital (PGO) wave-generating cells are involved in the generation of rapid eye movement (REM) sleep and REM sleep dependent cognitive functions. No studies to date have examined anatomical projections from PGO-generating cells to those brain structures involved in REM sleep generation and cognitive functions. In the present study, pontine PGO wave-generating sites were mapped by microinjecting carbachol in 74 sites of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
122
1
9

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 74 publications
10
122
1
9
Order By: Relevance
“…In the cat, PGO burst neurons with a short lead time (< 100 ms) prior to P-waves have been recorded in the parabrachial region which borders and overlaps with the subcoeruleus area recorded in this study in the rat (McCarley et al, 1978;Sakai and Jouvet, 1980;Nelson et al, 1983;Steriade et al, 1990;Datta and Hobson, 1994). Although neurons with these properties have also been recorded in other areas of the brainstem reticular formation, they seem to be particularly concentrated in the SubC area, which is consistent with this area being the best site to record P-waves Farber et al, 1980;Kaufman and Morrison, 1981) and the most sensitive site for carbachol to cause an enhancement of P-wave frequency (Datta et al, 1998).…”
Section: Responses To Carbacholsupporting
confidence: 87%
See 2 more Smart Citations
“…In the cat, PGO burst neurons with a short lead time (< 100 ms) prior to P-waves have been recorded in the parabrachial region which borders and overlaps with the subcoeruleus area recorded in this study in the rat (McCarley et al, 1978;Sakai and Jouvet, 1980;Nelson et al, 1983;Steriade et al, 1990;Datta and Hobson, 1994). Although neurons with these properties have also been recorded in other areas of the brainstem reticular formation, they seem to be particularly concentrated in the SubC area, which is consistent with this area being the best site to record P-waves Farber et al, 1980;Kaufman and Morrison, 1981) and the most sensitive site for carbachol to cause an enhancement of P-wave frequency (Datta et al, 1998).…”
Section: Responses To Carbacholsupporting
confidence: 87%
“…However, since we have shown that these neurons are hyperpolarized by carbachol and it has been previously demonstrated that carbachol causes a long-lasting enhancement of PGO waves in both rats and cats (Datta et al, 1991a;Datta et al, 1998) we suggest that this hyperpolarization is likely to be caused by acetylcholine released from neighbouring cholinergic neurons in the laterodorsal tegmental nucleus (LDT). This would also be consistent with the block of carbachol induced PGO waves in the cat by a M 2 receptor antagonist (Datta et al, 1993) since activation of M 2 receptors usually causes a hyperpolarizing response similar to the one we have observed here (Egan and North, 1986;Gerber et al, 1991).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 73%
See 1 more Smart Citation
“…It is well known that there are anatomical and physiological correlations between the amygdala and the pons, where the PGO wave generator is located (Calvo and Fernandez-Guardiola 1984;Datta et al 1998) and that the time interval between PGO waves and REMs is on the order of tens of milliseconds in neurophysiological studies using animals (Datta and Hobson 1994). In contrast, the BOLD response of the PGO areas started several seconds before the occurrence of REMs in the present study.…”
Section: Activation Accompanying Remcontrasting
confidence: 48%
“…Nuclei located in the pons, including the dorsal subcoeruleus nucleus (SubCD), are critical for generation of REM sleep (3,5,6,12,25,29,44). Lesion of this area produced REM sleep without muscle atonia or ponto-geniculo-occipital (PGO) waves (21,26,29,33), or diminished REM sleep (24).…”
mentioning
confidence: 99%